The protection racket - Games, Martin Hughes (Bristol : BBC-TV Production [production company] ; London : BBC Education & Training [distributor], 1994)
Describe on history of little weapon base on the nature little weapon from animals
Produced by BBC-TV Production in association with Lionheart Television International
Film editor, Sue Outlaw
Narrator: Richard Jobson
Keywords: Weapons